Hubungan Antara Rasa Syukur dengan Optimisme Pada Santri Pondok Pesantren Modern Islam (PPMI) Assalaam - Salim, Sagita Purbasari, Setiyo Purwanto, S.Psi, M.Si (2015)
Thank to God in live makes optimisme attitude, that emerges if we always thanks to God because optimisme attitude has believe healing when we are sick, success, failure, win and loose, happy when sad open expected, composed heeart from feel affraid, accumulate strong and get up spirit to pray helpong and tawakal to Allah. Everyone faithful believe with promise Allah. It is to be foundation santri study in boarding school always given religion science that to be foundation of them to always thanks to Allah. This research is 22 Novembre 2014 with sample research in boarding school Assalam of Sukoharjo. The writer takes sample with assume represent population are santri class XII, 2 classes santriawan and 2 classes santriwati are 98 students. Collecting data uses scale method that given to students. Analysis data shows coeficient correlation (r) is 0.774 with p = 0.00 (p < 0.01) so it means correlation positive very significance between thanks to God with optimisme of Santri modern boarding school Islam (PPMI) Assalam. If feeling thanks to God increases so optimisme a santri also increase, contrary if feeling thanks to God decrease so optimisme level of santri modern boarding school Islamic (PPMI) Assalam decrease. Base on analysis result variable scale feeling thanks to God shows mean empiric more large than mean hypotic (ME = 72.10 and MH = 57.5), it means feeling thanks to God level of santri is very high. Scale feeling optimisme of santri shows mean empiric is large than mean hypotic (ME = 65,18 and MH = 57.5) it means feeling optimisme of santri Assalam boarding school is very high. Effective contribution between feeling thanks to God to feeling optimisme of sanri Assalam boarding school is 60% that showed by coeficient determination (r²) is 0.600. it means 40% the other variables influence feeling optimisme of santri excuted variable feeling thanks to God like social environment of santri example relationship among santri, economic statue. Family's background and may be less knowledge of religion.